Evaluation of Menu Hierarchy Display Types in Self-Checkout System: Effects on Human Performance - Ahmad, N.; Radin Umar, R.Z.; Halim, I.; Mohamed, M.S.S.; Jamli, M. R.; Baharudin, M. S.; Hamid, M. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
Over the past few years, the retail industry especially in the US and UK supermarkets, has been experiencing a shift towards the self-checkout technology. Unfortunately, the self-checkout system is still far from perfect. There are many technological problems and design flaws that often irritate many shoppers such as the difficulty to find the item in the look-up directory. Menu hierarchy is one of the menu selection systems that is commonly used for many applications. The objective of this paper is to investigate the two types of menu hierarchy displays in the retail self-checkout system –graphical and non-graphical– and their effects on the human performance. The comparison between the two display types were made using the t-test by evaluating the completion time of the menu selections, the number of eye fixation and human errors made. The scope of this study is limited to the menu selection for produce items that need to be weighed at checkout. The study finds that there is not enough statistical evidence to conclude that the menu hierarchy system with the graphical display will result in faster performance in the retail self-checkout system than the one without the graphical display.